Testing, modelling and design of hot-rolled stainless steel channel sections under combined compression and minor-axis bending moment - Li, Shuai (2022)
Experimental and numerical studies on hot-rolled stainless steel channel sections subjected to combined compression and minor-axis bending moment have been conducted and are fully reported in the present paper. The testing programme included initial local geometric imperfection measurements and ten minor-axis eccentric compression (combined loading) tests. The numerical modelling programme comprised a validation study, where finite element models were developed and validated against the test results, and a series of parametric studies, where the developed finite element models were adopted to generate further numerical data over a wide range of cross-section dimensions and loading combinations. The experimentally and numerically obtained data were used to assess the accuracy of the design interaction curves for hot-rolled stainless steel channel sections under minor-axis combined loading, as given in the European code and American specification. The assessment results generally reveal that the design interaction curves provided in the main body of the two design codes lead to unduly conservative and scattered failure load predictions, mainly owing to the conservative end points (i.e. the cross-section compression and bending resistances), which are calculated without considering material strain hardening. The appendix of each design code also provides an alternative method that uses the continuous strength method to account for material strain hardening in calculating the end points of the design interaction curve, and is shown to result in much more accurate and consistent predictions of failure load for hot-rolled stainless steel channel sections under combined compression and minor-axis bending moment.